Thermal and pasting properties of cassava starch-dehydrated orange pulp blends (Scientia Agricola, 2011)
Instant mixtures are easy to prepare and frequently present functional appeals. A quality parameter for instant mixtures is their rheological behavior. This study aimed at evaluating the effects of extrusion parameters on the pasting properties of cassava (Manihot esculenta L.) starch and dehydrated orange (Citrus sinensis (L.) Osbeck) pulp mixtures. The variable parameters were moisture of mixtures (12.5 to 19%), barrel temperature (40 to 90ºC) and screw rotation (170 to 266 rpm). The extruded mixtures did not show gelatinization enthalpy. Moisture had the greatest effect on paste properties. The initial pasting viscosity (before heating) of RVA (Rapid visco analyzer) is the most relevant parameter to instant mixtures. The highest cold viscosity values were obtained when mixtures were extruded under high moisture and high screw speed. High moisture (19.5%), intermediate temperature (65ºC) and screw speed (218 rpm) led to extruded mixtures production with low component degradation.